Medierea conflictelor - o soluție viabilă pentru depășirea barierelor comunicaționale. Implicarea Uniunii Europene în conflictul ruso-ucrainean în timpul crizei gazelor naturale - Cosmin IRIMIEŞ; Laura MARUŞCA (Revista Transilvană de Ştiinţe Administrative, 2009)
The premises of this project are that approximately 90% of the conflicts in the modern society and not only, are based on poor communication. Any type of miscommunication (due to cultural, linguistic, politic or religious differences) can and will generate conflicts of various intensities going from simple quarrels to diplomatic incidents and all the way to wars. The mediator has the role to solve any existing conflict and to help repair the breaches from the communicational system between parts, in order to preserve the relationship. The article presents a case study on the involvement of the European Union’ structures to amicably solve the conflict triggered during 2008 - 2009, between the Russian Government and the Ucrainean one regarding the gas provisions and the price claimed for the natural gas sold to European countries.